Sistem Operasional Dalam PT. BPRS Jabal Tsur Pandaan Kabupaten Pasuruan: Operational System in PT. BPRS Jabal Tsur Pandaan, Pasuruan Regency - Mariyah Ulfah (LP2M Universitas Islam Negeri Kiai Haji Achmad Siddiq Jember, 2017)
The limited penetration of Islamic microfinance institutions in rural East Java poses a critical challenge to inclusive economic growth, particularly in communities requiring sharia-compliant banking. Grounded in agency theory and Islamic contract law (fiqh muamalah), this study identifies a gap between theoretical product classifications and actual implementation in small-scale Islamic rural banks. This research aims to describe the operational system of PT. BPRS Jabal Tsur Pandaan, focusing on its fund-raising and fund-distribution mechanisms. A qualitative descriptive method with a phenomenological approach was employed, utilizing structured interviews with the director and documentary analysis of the bank’s 2007 feasibility study and bulletins. The most important findings reveal that fundraising products include wadiah (custodianship: qardhiyu, haji, qurban, ZIS) and mudarabah (profit-sharing: general savings and deposits), while financing is dominated by murabahah and musyarakah contracts. Performance data showed a 36% increase in margin/profit-sharing income, a 24% rise in savings, and 4% asset growth, though realized financing declined by 34% in April. The study concludes that BPRS Jabal Tsur effectively applies dual Islamic contract systems but faces monthly volatility in financing realization. It is recommended that the bank strengthen risk management and liquidity buffers to stabilize monthly financing performance. Keterbatasan penetrasi lembaga keuangan mikro syariah di pedesaan Jawa Timur merupakan tantangan krusial bagi pertumbuhan ekonomi inklusif, terutama di komunitas yang membutuhkan layanan perbankan sesuai syariah. Berlandaskan teori agensi dan hukum kontrak Islam (fiqh muamalah), penelitian ini mengidentifikasi kesenjangan antara klasifikasi produk teoretis dan implementasi aktual pada BPR syariah skala kecil. Penelitian ini bertujuan mendeskripsikan sistem operasional PT. BPRS Jabal Tsur Pandaan, khususnya mekanisme penghimpunan dan penyaluran dana. Metode deskriptif kualitatif dengan pendekatan fenomenologis digunakan, melalui wawancara terstruktur dengan direktur dan analisis dokumen studi kelayakan serta buletin tahun 2007. Temuan terpenting menunjukkan bahwa produk penghimpunan dana meliputi wadiah (qardhiyu, haji, qurban, ZIS) dan mudharabah (tabungan umum dan deposito), sementara pembiayaan didominasi akad murabahah dan musyarakah. Data kinerja menunjukkan peningkatan pendapatan margin/bagi hasil 36%, tabungan naik 24%, dan aset tumbuh 4%, meskipun realisasi pembiayaan menurun 34% di bulan April. Penelitian menyimpulkan bahwa BPRS Jabal Tsur efektif menerapkan sistem akad ganda syariah namun menghadapi volatilitas bulanan realisasi pembiayaan. Direkomendasikan agar bank memperkuat manajemen risiko dan buffer likuiditas untuk menstabilkan kinerja pembiayaan bulanan.